Treinamento em serviço : formação de professoras e professores não titulados no Projeto Logos II em Alta Floresta, Mato Grosso (1980-1993) - Luz, Rosemary da (2018)
This research analyzes the Logos II Project, a formation project for lay teachers that acted in classrooms in urban and rural schools without specific qualification to act in the teaching profession instituted by the Ministry of Education and Culture –MEC, with the support of the Department of Supplementary Education- SDU, in Mato Grosso, more specifically in the municipality of Alta Floresta. For the development of Logos II Pedagogical centers were created in several Brazilian regions. In the state of Mato Grosso, sixty-six Pedagogical Centers (PC) were created in several cities of Mato Grosso. In Alta Floresta was created the Pedagogical Center number 13. We have as objectives: evaluate how Logos II was implemented in the State of Mato Grosso, as well as analyze and record the course and the development of the Project in Alta Floresta from 1980 to 1993. We try to answer: How was the implementation of the Logos II project for the training of lay teachers in Alta Floresta - Mato Grosso from 1980 to 1993? How were the pedagogical meetings organized at the Pedagogical Center of Alta Floresta? How were the development of the sessions of teaching micro? Were most o the female students? The categories of analysis are a) Historical context, origin, creation, installation of Logos II, b) Standards and regulations, c) Profile of course students and guiding of Logos II: origin, formation and performance, d) Curriculum,disciplines, textbooks, methods and teaching tools. We have as research sources the resolutions, the state decrees, the operating rules, micro-education modules, crafts, enrollment forms, school history, license plates, teaching micro evaluation, copybook of field, record minutes of pedagogical meetings and photos. This documentation was collected in different files, such as: Center for Youth and Adult Education – CYAE Ariosto da Riva, Memory Institute of the Legislative Power of Mato Grosso, Public Archive of Mato Grosso, School Documentation Archive of the Education Department of the state of Mato Grosso, among others. Authors as Jacques Le Goff (1990), Marc Bloch (2002), Paolo Nosella e Ester Buffa (2009), Carlo Ginzburg (1989), Peter Burke (1997) made possible the understanding of the analysis of the documents, the historical memory and the methodological paths of the investigation. Theoretical studies of Carlos Rodrihues Brandão (1986), Mirian Jorge Warde (1986), Iraçi Silva Picanço (1986), José Cerchi Fusari (1990) Marimar Muller Stahl (1982,1986), helped us in the input of lay teachers in classrooms. Maria Lúcia de Arruda Aranha(2006¨), Vanilda Pereira Paiva(1987),Sud Menucci (2006), Manoel Bergström Lourenço Filho (2001) Sergio Celani Leite(1999) have expanded our knowledge about the History of Education and the rural teacher in Brazil. Jane Soares de Almeida (1998), Guacira Lopes Louro (2001), Michelle Perrot (2017), Maragreth Rago (2001) were essential to understand the education of women. The analysis of the sources allowed us to infer that Project Logos II which enabled the formation of lay teachers who worked in the first primary series and did not have specific qualification to act in the teaching, schools in the urban and rural areas of the state of Mato Grosso, but specifically in Alta Floresta.